Pengaruh Stres Kerja dan Beban Kerja Terhadap Kinerja Karyawan Pada PT. Nipro Indonesia Jaya Karawang - Fatiha, Reisa Alika; S, Sungkono (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of the study was to determine the effect of work stress and workload partially on employee performance at PT Nipro Indonesia Jaya and the effect of work stress and workload simultaneously on employee performance at PT Nipro Indonesia Jaya. This research was conducted using quantitative methods. The population used was 100 people in the employees of PT. Nipro Indonesia Jaya, while the sample taken by researchers was 30 people., considering the population is not too large, it uses Proportional Random Sampling technique. The results of the analysis revealed that work stress and burnout had a positive and significant impact on employee performance. The regression coefficient for stress at work is 0.132, which means stress will increase the worker's productivity by 0.132. Furthermore, the regression coefficient for work is 0.405, implying that every increase in one unit of work will result in a 0.405 unit increase in employee productivity. This demonstrates that effective work stress management and scheduling can improve employee productivity and efficiency. However, unrealistic work demands can lead to burnout and a decrease in work quality. As a result, managers must ensure that work hours are properly managed in order to maximize employee productivity and well-being.